THE INVESTIGATION OF CAHIT ZARIFOĞLU’S NOVEL CALLED “SAVAS RITIMLERI” BY DISCOURSE ANALYSIS METHOD - Ahmet USLU (Fırat University, 2019)
The number of interdisciplinary studies on social sciences has been increasing recently. In the present study, Cahit Zarifoğlu’s novel called “Savaş Ritimleri” is examined by employing discourse analysis method especially used in Sociology and Communication fields. The author is focused on social issues with his own perspective. He reflects his views on the literary work by going through different ways, which is generally and often observed in literary works centering on historical and political issues. Zarifoğlu is interested in invasion of Afghanistan by USSR (Union of Soviet Socialist Republics). While he tells about the liberation battle, he composes his own discourse through his own views and ideology. As the novel is based on actual events, the author gives clues about his discourse in the novel. In the current study, it is attempted to investigate the discourse presented in Zarifoğlu’s novel via Gee’s discourse analysis method. According to this method, the discourse of the author in the novel has been examined under three titles. The present literary work has been scrutinized under twenty-seven subtitles led by titles which are called style analysis, semantic analysis and linguistic analysis. Regarding the style analysis, the tools that are used while the author composes his discourse are put forward and it is correlated to novel’s fictional structure. As for semantic analysis, semantic relations that create discourse are explained by considering structural elements. Finally, with respect to linguistic analysis, the words that the author has specifically selected to use and the structures that the author has chosen are presented explicitly. The main purpose of the present paper is to indicate the fact that the discourse analysis is one of the most effective methods for literary work analysis and for being understood by the readers.